2018
DOI: 10.1038/s41598-018-27545-4
|View full text |Cite
|
Sign up to set email alerts
|

QSAR-based molecular signatures of prenylated (iso)flavonoids underlying antimicrobial potency against and membrane-disruption in Gram positive and Gram negative bacteria

Abstract: Prenylated flavonoids and isoflavonoids are phytochemicals with remarkable antibacterial activity. In this study, 30 prenylated (iso)flavonoids were tested against Listeria monocytogenes and Escherichia coli (the latter in combination with an efflux pump inhibitor). Minimum inhibitory concentrations of the most active compounds ranged between 6.3–15.0 µg/mL. Quantitative structure-activity relationships (QSAR) analysis was performed and linear regression models were proposed with R2 between 0.77–0.80, average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 56 publications
(72 reference statements)
9
49
0
Order By: Relevance
“…In addition, we detected that the DNA and RNA exudations of S. aureus, E. coli and P. aeruginosa were also remarkably enhanced after the administration of flavonoids in A. conyzoides for 2 hours. There have been several evidences showed that flavonoids could exert their antibacterial actions via inducing membrane permeabilization [14][15][16]. Hence, we speculate that the antibacterial mechanism of flavonoids in A. conyzoides is that they can also cause membrane permeabilization and consequent nucleic acid exudation in bacteria.…”
Section: Agingmentioning
confidence: 84%
“…In addition, we detected that the DNA and RNA exudations of S. aureus, E. coli and P. aeruginosa were also remarkably enhanced after the administration of flavonoids in A. conyzoides for 2 hours. There have been several evidences showed that flavonoids could exert their antibacterial actions via inducing membrane permeabilization [14][15][16]. Hence, we speculate that the antibacterial mechanism of flavonoids in A. conyzoides is that they can also cause membrane permeabilization and consequent nucleic acid exudation in bacteria.…”
Section: Agingmentioning
confidence: 84%
“…In previous studies, licoricidin has been reported to exert antibacterial activity against Porphyromonas gingivalis and Prevotella intermedia, two periodontal pathogens [ 21 ] as well as against the endodontic pathogen Enterococcus faecalis [ 22 ]. Although we did not investigate the mechanism of antibacterial action of the isoflavans tested, a previous study by Araya-Cloutier et al [ 23 ] showed that glabridin causes membrane permeabilization as determined by the uptake of the fluorescent probe propidium iodide. Other flavonoids isolated from licorice root, including 1-methoxyficifolinol, 6,8-diprenylgenistein, 6,8-diisoprenyl-5,7,4′-trihydroxyflavone, gancaonin G, glycyrrhizol A, glycyrrhizol B, and licorisoflavan A have also been reported to exhibit antibacterial activity against S. mutans [ 17 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…It should be especially noted that several of the selected molecular descriptors were described previously as important for statistically significant separation between antibacterial and nonantibacterial compounds (Araya-Cloutier et al, 2018). Distributions for the representative descriptors used for learning herein are depicted in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%